Comparative advantage and policy measurement of production of selected food crops in Iran - Vakilpoor, Mohammad Hassan (2012)
The food crop sector in Iran plays an important role in the economy. In 2000 – 2008, it contributed about 11 percent to the country’s GDP, and approximately 23 percent of non-oil exports. In order to reduce the dependency on oil export and to enhance the level of food self-sufficiency, food production has been emphasized by the government as mentioned in the policies of guaranteed purchase for crops and subsidizing inputs. This study aims to investigate the comparative advantage of selected food crop production, namely, wheat, barley, potato, rice, and corn, and recommend policy instruments for improvement of the selected food crop. The Domestic Resource Cost (DRC) was employed to measure the comparative advantage of the selected food crops in five regions: Northern, Southern, Central, Eastern, and Western. The Nominal and Effective Protection Coefficients were used to measure the magnitude of the government interventions. The DRC was computed through the Policy Analysis Matrix (PAM) method. Shadow prices of domestic resources were calculated through estimation of Cobb-Douglas production function by using panel data models. The general results of the study indicated comparative advantage for all selected food crop production, except rice, in the study period (2001-2008). Besides, government has paid subsidy on inputs in production of all selected crops, but in contrast, it has imposed direct and indirect taxes on crops in related market more than inputs subsidies. The resultant of these polices in selected crops production (except rice) have been not in favor of farmers that indicated total protection policy in crops production has been neutralized. The specific results of the comparative advantage and supports of products and inputs in crop - region level, revealed that the barley production had a comparative advantage except in the Eastern and Southern regions. The DRC for the entire country is obtained to be less than one (0.90), suggesting a comparative advantage in the production of barley in country level. While corn has a comparative advantage only in production of Western region and also average of this indicator for country is equal to 0.99 that showed the country has a brittle comparative advantage. The lowest DRC in this study belongs to the rice with a quantity equal to 2.01, that showed the north region and also in country level while this crop has a disadvantage. Potato has a strong comparative advantage among the studied crops. The DRC of this crop in all regions and country is less than one, which indicated that Iran has a notable value of comparative advantage in production of potato. The results of DRC for wheat illustrated that all regions (except Southern) have a comparative advantage. A DRC equal to 0.94 for the whole country suggest a comparative advantage in production of this crop. Finally, investigation of the government intervention showed that NPCO for all products in all regions (except in rice) were computed to be less than one. This implies that the government imposed a tax on the production of these crops. While NPCI for all commodities, all regions and also the whole country were computed less than one which suggests the producers received subsidies for all tradable inputs. The results of the EPC were computed to be less than one for four products. This indicates that government received implicit tax from producers of barley, potato, corn, and wheat which implies the resultant of this intervention was detriment to producers of mentioned crops. Some of the important implications of this study are as follows: (1) the products include wheat, barley, corn, and potatoes have mainly comparative advantages. Therefore, the expansion of these crops in all regions is recommended. Rice production is recommended in order to improve the production methods and to choose the high yielding varieties; (2) the results show that the government have subsidies inputs in production of all crops in whole regions. Supporting the products that have comparative advantage in production is reasonable. In contrast, protection of the products that had comparative disadvantage is considered waste of resources; (3) the intervention of government in crops markets (exception of rice) was detriment to the farmers, so it is recommended to the government to avoid intervention in the crops market and also to allocate guaranteed purchase to the regions that have the highest comparative advantage;(4) the resultant of government intervention in inputs and outputs markets including wheat, corn, barley and potatoes was detriment to the farmers, so it is recommended to the government to adopt policies that will be a positive resultant of interventions.